Paraspinal Muscles of Patients with Lumbar Diseases - Park, Moon Soo; Moon, Seong-Hwan; Kim, Tae-Hwan; Oh, JaeKeun; Lee, Seon-Jong; Chang, Ho Guen; Shin, Jae-Hyuk (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Objective The treatment of atrophy or increased fat infiltration of the lumbar paraspinal muscles of patients with back pain, lumbar radiculopathy, or lumbar degenerative kyphosis is controversial. We review the literature on changes in the lumbar paraspinal muscles of these patients.Methods We searched Medline for relevant English-language articles and retrieved 25 articles published from 1993 to 2017 on changes in the lumbar paraspinal muscles; 21 met our study criteria. We categorized each article into three groups: randomized clinical trial, nonrandomized prospective study, or retrospective study.Results We found 1 randomized prospective, 3 nonrandomized prospective, and 17 retrospective studies. Atrophies of the multifidus muscle are found at the level of the L5 vertebral body in patients with back pain, lumbar radiculopathy, and lumbar degenerative kyphosis. Increased fat infiltration to the multifidus muscle was found in the patients with lumbar radiculopathy or lumbar degenerative kyphosis. However, there are controversies over fat infiltration to the multifidus muscle in the patients with back pain and the efficiency of a paramedian surgical approach to prevent the atrophy of the multifidus muscle.Conclusions Atrophy of the multifidus muscle was found in patients with back pain, lumbar radiculopathy, and lumbar degenerative kyphosis. There was increased fat infiltration to the multifidus muscle in those patients with lumbar radiculopathy or lumbar degenerative kyphosis.
Keywords: paraspinal muscles; lumbar spine; radiculopathy; degenerative lumbar kyphosis